Epidermolysis bullosa - Anđelić Slađana; Stefanović Ivana; Tasić-Uroš Danijela; Milivojčević- Bevc Ivana; Savić Nikola (Halo 194)
Epidermolysis bullosa (EB) is a hereditary multisystemic disease caused by genetic defects in the skin's structural proteins. Depending on the type of disease, symptoms vary from localised fragility and bullae to a widespread generalised form, including extracutaneous manifestations. In the most severe forms, EB causes death in the earliest period of life. The treatment of EB is complex and usually requires the involvement of several different specialists. Without curative therapy, treatment is oriented towards supportive care, symptom control, and preventing mild to severe complications. Vector gene therapy Vyjuvek (beremagene geperpavec), based on the herpes simplex virus type 1, is a new hope for treating wounds in patients older than six months who suffer from dystrophic forms of EB.